Degradation behavior of Ti-Nb alloys: Corrosion behavior through 21 days of immersion and tribocorrosion behavior against alumina. (1st May 2020) - Çaha, I.; Alves, A.C.; Kuroda, P.A.B.; Grandini, C.R.; Pinto, A.M.P.; Rocha, L.A.; Toptan, F.
Highlights: Corrosion behavior of alloys was studied through an immersion period of 21 days. Degradation mechanisms were significantly affected by their microstructure. The β-type alloy presented lower corrosion and wear resistance than the α+β-type one. Abstract: Non-toxic and allergic free β-type Ti alloys are attractive metallic implant materials due to their lower Young's modulus and good biocompatibility, but the corrosion and tribocorrosion behavior are yet to be fully understood. In this study, corrosion behavior of Ti-15Nb and Ti-40Nb alloys was investigated and compared with the commercial Ti-6Al-4V alloy through an immersion period of 21 days. The tribocorrosion behavior was investigated under open-circuit potential by using a ball-on-plate tribometer. Results suggested that the β-type Ti-40Nb alloy having 51 GPa Young's modulus had lower corrosion and wear resistance as compared to the α + β-type Ti-15Nb and Ti-6Al-4V alloys.